Экспериментальное исследование переходных процессов в программно-аппаратном устройстве цифровой фазовой автоподстройки частоты - Бондарев, А П.; Алтунин, С.И. (Технология и конструирование в электронной аппаратуре, 2016)
Работа посвящена экспериментальному исследованию переходных процессов, возникающих в устройстве цифровой фазовой автоматической подстройки частоты (ЦФАПЧ) после замыкания петли обратной связи. Для решения поставленной задачи была выполнена программно-аппаратная реализация устройства ЦФАПЧ. В статье приведена структурная схема устройства и описана его математическая модель. Рассмотрен процесс захвата частоты гармонического колебания и проанализировано влияние основных параметров устройства (собственной частоты и коэффициента затухания) на продолжительность переходного процесса. Приведены графики ключевых сигналов устройства для оценки продолжительности переходного процесса. Результаты экспериментального исследования программно-аппаратного устройства ЦФАПЧ сопоставлены с результатами исследования его имитационной модели. Робота присвячена експериментальному дослідженню перехідних процесів, що виникають у цифровому пристрої фазового автоматичного підстроювання частоти (ЦФАПЧ) після замикання контуру зворотнього зв’язку. З цією метою була проведена програмно-апаратна реалізація пристрою ЦФАПЧ. В статті наведено структурну схему пристрою ЦФАПЧ і описано його математичну модель. Розглянуто процес захоплення частоти гармонічного коливання та проаналізовано вплив основних параметрів пристрою ЦФАПЧ (власної частоти та коефіцієнта затухання) на тривалість перехідного процесу. Наведено графіки ключових сигналів пристрою ЦФАПЧ для оцінки тривалості перехідного процесу. Результати експериментального дослідження програмно-апаратного пристрою ЦФАПЧ співставлені з результатами дослідження його імітаційної моделі. This article considers the experimental research of transient processes that occur in digital phase-locked loops (DPLL) after closing the feedback loop. Firmware implementation of DPLL device was made for this purpose. The paper shows the block diagram of the DPLL and describes its mathematical model. In particular, the location of poles and zeros of DPLL transfer function was determined by the transfer function of the 2nd order analog PLL and the formulas for digital filter coefficients were deducted. The article also represents the block diagram of hardware part of the firmware DPLL. Its key part is the STM microcontroller which is connected to the PC. For convenience reasons, the unique interface between the microcontroller and the PC was created in order to present waveforms of several signals simultaneously. Moreover, the paper depicts the algorithm of software part of the firmware DPLL in general as well as the detailed algorithm of voltage-controlled oscillator (VCO) operation РІР‚вЂњ it works as direct digital synthesizer (DDS). The experimental research of the frequency acquisition process of harmonic oscillation was performed for three different sets of DPLL parameters. For each case the location of DPLL poles and zeros and plots of DPLL key signals (tracking error, current frequency and phase of output signal) were shown. Obtained diagrams demonstrate that a change of the DPLL natural frequency and damping factor influences on the transient process duration. Pictures signal waveforms from oscilloscope confirm these results. Furthermore, the results of the firmware DPLL research correspond to investigation results of existing simulation model of this DPLL with sufficient accuracy.